Effects of aging on laser evoked potentials. Issue 5 (31st March 2015) - Creac'H, Christelle; Bertholon, Alexandre; Convers, Philippe; Garcia‐Larrea, Luis; Peyron, Roland
ABSTRACT: Introduction : Aging has been reported to reduce the amplitude of laser evoked potentials. However, it is unknown whether this effect depends on the length of the sensory fibers. This is an important issue, because most painful neuropathies are length‐dependent. Methods : We conducted a study of 40 healthy subjects, half of whom were older than age 50 years. Nociceptive stimuli were delivered to the feet and thighs using a CO2 laser stimulator. Results : Detection and pain perception thresholds did not correlate with age. Latencies of N1, N2, and P2 correlated positively with age on the feet but not on the thighs, whereas the amplitude of N2‐P2 decreased with age for both areas. Conclusions : The effects of aging on latencies may reflect a distal loss of peripheral inputs and a length‐dependent de‐synchronization of the ascending nociceptive volley. Additional changes in peripheral and central processes may explain the diffuse decrease of N2‐P2 amplitudes observed with aging. Muscle Nerve 51 :736–742, 2015